Household Endowments and Poverty Reduction in Rural Nigeria: Evidence from Rice Farming Households - Awotide, B.A.; Diagne, A.; Awoyemi, T.T.; Ojehomon, V.E.T. (Science Alert, 2011)
This study empirically investigated the role of household endowments in determining poverty among the rice farming households in Nigeria. A total of 600 rice farmers selected through multistage random sampling techniques were interviewed with the aid of well structured questionnaires. The data collected were analysed using descriptive statistics, FGT and logit model. Household endowments were classified into human assets, physical assets and financial assets. The results of the logistic regression revealed education of the household heads, access to mobile phone, amount of credit obtained, farm size, irrigation facility, possession of livestock, television set, radio set and number of rooms in a house have a poverty decreasing effect. Although, only number of rooms in the house is statistically significant. This implies that as these variables increase the probability of being poor will decrease. The result of the marginal effects also revealed that an additional increase in the number of rooms will reduce the probability of being poor by 3%. Other variables such as toilet facility and household size were also significant and positively related to the probability of being poor. Strategies, policies and programs that will lead to increase in the household endowments should be put in place. The introduction of good toilet facilities and sanitation should be embarked upon and education on the need for family planning should be increased if poverty is to be reduced or eliminated in the study area.